El valor referencial y los procesos de selección para las adquisiciones y contrataciones en la universidad nacional toribio rodríguez de mendoza de amazonas 2006-2010 - Alvarado Zuta, Milagritos Catterine (2014)
The subject of this research shows the effect of the determination of estimated value in the execution of the selection processes for the procurements and acquisitions of goods, services and works at the National University Toribio Rodriguez de Mendoza of Amazonas from 2006 to 2010. The methodological sequence considers the following steps: select the contract files to be evaluated, establish and identify the methodology and procedures for determining the estimated value of different types of selection processes and evaluate the influence of determining the estimated value in the execution of the selection process. The results show that determination of the estimated value significantly influences in execution of the selection process and therefore in the efficiency of public procurement to fulfill organizational objectives.